IPGRI in the Americas: Regional report - Americas 1999-2000 - International Plant Genetic Resources Institute (2001)
This report highlights some particularly significant achievements of IPGRI's activities in the Americas in1999 - 2000 and describes the impact that this work is having. It contains examples of how the Institute responds to the challenges and opportunities of the Americas. The collaborative activities described in this report are examples of how diversity can lead to development. These examples are evidence of our fundamental commitment to the people and plant genetic diversity of the Americas. We hope our readers enjoy this publication and continue supporting IPGRI's efforts to safeguard and promote the sustained use of the incomparable agrobiodiversity in the Americas for the well-being of present and future generations.